Review on the Effect of Geometrical Parameter on Heat Transfer Performance for LED - Jadhav, A. R.; Kumbhar, S. V.; Pol, G. J. (Asian Review of Mechanical Engineering, 2020)
LED lamp use increases day by day. In LED about 80% of energy is converted into heat. Excess heat causes a decrease in life as well as illumination efficiency. In this paper, we reviewed the different techniques used for the cooling of the LED. Generally, the passive method is preferred in the cooling of the LED. An experimental and numerical study was done by the researcher to obtain optimum arrangement for heat dissipation from the heat sink of the LED. Qie shen discussed the effect of orientation of fin on a rate of heat transfer. Hao wegang studied the effect of fin length fin height synergy angle on thermal resistance. Yicang Huang carried out a numerical simulation of the different arrangements of heat sinks like conventional and OPF and PPF.